VD_FINDINFO Décision / 2011 / 426 vom 11. August 2011 - VD Tribunal cantonal (2011)
RISQUE DE FUITE, DÉTENTION PRÉVENTIVE, PROPORTIONNALITÉ | 140 CPP (CH), 147 al. 3 CPP (CH), 150 CPP (CH), 221 al. 1 let. a CPP (CH), 222 CPP (CH), 229 CPP (CH)